2017
DOI: 10.5339/jemtac.2017.1
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure injection injury: Role of early detection and aggressive intervention

Abstract: Emergency department physicians can easily underestimate the severity of damage underlying the innocuous looking high-pressure injection injuries. These work-related injuries lead to significant lifelong morbidity as functionality is compromised in most cases, even after recovery due to high rates of amputation. Hence it is important to consider all high-pressure injection injuries as surgical emergencies. A detailed case history including pressure of the instrument, nature of the material, volume injected, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Bashir et al, (2017) [37] reported this correlation, showing an increase of the amputated subjects who had been treated after 10 h from injury. We found no strict correlation between the time (hours) of treatment after trauma and its outcome.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Bashir et al, (2017) [37] reported this correlation, showing an increase of the amputated subjects who had been treated after 10 h from injury. We found no strict correlation between the time (hours) of treatment after trauma and its outcome.…”
Section: Discussionmentioning
confidence: 86%
“…At the follow-up, a significantly better VAS was detected in the subjects treated ≤6 h from an accident. This could be put down to an early treatment of the phlogosis process caused by the material and the probable complications such as necrosis [37].…”
Section: Discussionmentioning
confidence: 99%